LEARNING STYLES AND VOCABULARY ACHIEVEMENT - Sri Minda; Purnama Rika Perdana (Lingua, 2023)
ABSTRACT This study aims to determine whether there is an influence of learning styles on the acquisition of English vocabulary. This study investigates whether there is an effect of visual, auditory and kinesthetic learning style on English vocabulary. This type of research is correlation research. The population of this study were second grade students of SMA Negeri 1 Padangsidimpuan. The number of samples in this study were 50 students who were randomly selected. To collect data, the researcher used a questionnaire and a vocabulary test. Questionnaires are given with the aim of knowing student learning styles. The researcher made observations in class when there was an English subject. The data obtained was tested by t-test to find out whether the learning style is significant to the acquisition of English vocabulary. The data shows that there are 14 (28%) students who are visual learners, 13 (26%) students with an auditory style and 23 (46%) as kinesthetic students. From the results of the hypothesis test it was found that the calculated value obtained was 0.694 and compared with the alpha table value of 0.05, the calculated value was greater than the table value. It states that there is a very strong influence between learning styles and English vocabulary. In other words, learning styles affect students' grades, especially English. Keywords: visual, auditory, kinesthetic, and vocabulary achievement.